Shotgun metagenomics reveals the interplay between microbiome diversity and environmental gradients in the first marine protected area in the northern Arabian Gulf - Fakhraldeen, Saja A.; Madhusoodhanan, Rakhesh; Habibi, Nazima; Al-Haddad, Sakinah; Alagarsamy, Surendraraj; Habeebullah, Sabeena F. K.; Al-Zakri, Walid M.; Thuslim, Fathima; Fernandes, Loreta; Al-Yamani, Faiza; Al-Said, Turki (Frontiers in Microbiology, 2025)
IntroductionThe northwest Arabian Gulf encounters significant anthropogenic pressures, including nutrient enrichment from coastal development and effluent discharge.MethodsThis study presents the first shotgun metagenomics-based characterization of microbial communities in Kuwaiti waters of the northwest Arabian Gulf, focusing on Kuwait’s first Marine Protected Area (MPA) in Sulaibikhat Bay, a vital nursery ground for commercially important fish.ResultsAnalysis revealed significantly higher microbial diversity within the MPA compared to adjacent waters, with Rhodobacteraceae (27.8%) and Flavobacteriaceae (15.3%) being dominant. Elevated inorganic phosphorus, nitrogen, and salinity were key factors driving this diversity. Multivariate analysis highlighted phosphate as a critical component affecting the MPA microbial community structure, particularly for the families Microbacteriaceae, Flavobacteriaceae, and Rhodobacteraceae.DiscussionThis study underscores the ecological importance of MPAs and highlights the impact of nutrient enrichment and other environmental stressors on microbial diversity, emphasizing the need to reduce nutrient influx to mitigate eutrophication and enhance marine ecosystem resilience in stressed environments.